Review of Self-sensing Capability of Ultra-high Performance Concrete - Lian, Jinkang; Hu, Chao; Fu, Tengfei; Wang, Yulin (Frontiers in Materials, 2021)
UHPC has the inherit potential to self-sensing capability due to its inclusion of steel fibers or other electrically conductive materials. Many studies have investigated the electrical and piezoresistive properties of UHPC. With the incorporation of micro steel fibers, carbon nanotubes, carbon nanofibrils, or nano graphite platelets, it opens up great potential to allow UHPC to effectively sense stress, strain, and crack damage. Therefore, the UHPC-based structures can achieve the functionality of structure health monitoring (SHM). This article reviews the recent advances in self-sensing capability of various UHPC-based materials with the focus on sensing capability and mechanisms. Future applications and challenges are also discussed.